Greener synthesis and characterization of silver nanoparticles using murraya koenigii leaf extract and its antibacterial activity - SHARMILA DEVI R; SEBASTIAN ANTONY SELVAN C (International Journal of Pharma and Bio Sciences, 2017)
The green synthesis of nanoparticles from plant sources is simple, rapid and ecofriendly approach. In the present work synthesis and characterization of silver nanoparticles, and their antimicrobial effect on bacteria were studied. The novelty in this work, is the Murraya koenigii leaves present throughout the year and not an seasonable leaves and it has many medicinal properties. The synthesized silver nanoparticles loaded with activated carbon is used in adsorption studies and obtained good results. In the process of synthesizing silver nanoparticles using Murraya koenigii leaves extract, observed rapid reduction (i.e. within 20 minutes) of silver ions leading to the development of stable silver nanoparticles in the solution. The synthesized silver nanoparticles (AgNPs) were characterized by Ultraviolet-visible (UV-Vis) spectrometer, Fourier Transform Infrared spectroscopy(FTIR), X-ray diffraction study(XRD), SEM(Scanning Electron Microscopy) and antibacterial activity. Synthesized silver nanoparticles were confirmed by analyzing the excitation of surface plasmon resonance (SPR) using UV-Vis spectrometer at 433nm. The observed peaks in XRD pattern corresponding to (111), (200) and (311) planes. Disc diffusion method was used to determine the zone inhibition of the tested samples by using two gram positive and two gram negative bacteria and it has zone of inhibition from the range of 13.2mm to 23.4 mm. The silver nanoparticles are prepared by using Murraya koenigii leaves extract have potent antibacterial activity and cost wise is very cheap and ecofriendly to the environment.